Verbalization of the concept language policy: Online research - Anisimova, Alla I.; Safonova, Nataliia A.; Dobrushyna, Mariia Yu.; Lysenko, Nataliia O.; Bezrodnykh, Iryna H. (Linguistics and Culture Review, 2021)
The article deals with the issues of revealing the semantic structure of the concept Language Policy based on the online experiment. Most participants of the experiment represent Ukraine and European countries such as France and Germany, Poland and a few respondents from the USA and Turkey. The analysis of the similarities and differences of the concept Language Policy established via an associative experiment done with the help of respondents from different countries helps to outline their national specific features, which contribute to a deeper understanding of both foreign and native languages and cultures through the analyses of the semantic structure of the concept in question. It is emphasized that Language Policy has become a widespread phenomenon in modern Ukrainian and European societies from the social point of view. The study of a linguistic situation in a society can be considered to be an important means of forming the ability to conduct intercultural dialogues. As for the methods and linguistic tools they can vary depending on the applicable target. The article identifies common and different aspects in of the field structures of the concept Language Policy done in multilingual sociolinguistic surroundings.